Pengaruh Investasi Asing dan Pertumbuhan Ekonomi Terhadap Pengangguran di Pulau Sumatera - Nessya Wafa Nasyla; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
The aim of this research is to find out how economic growth and foreign investment affect the unemployment rate. The data used consists of panel data from 10 Sumatran provinces from 2011 to 2019. The analysis model uses panel regression with a fixed effect approach. Research finds that foreign investment has a negative and significant influence on increasing the unemployment rate, so increasing foreign investment can reduce the unemployment rate on the island of Sumatra. It was also found that economic growth had a negative and significant effect on increasing unemployment. Therefore, the higher the level of economic growth in a region, the lower the unemployment rate. The implication of these findings is that the contribution of foreign investment and economic growth is needed to reduce unemployment rates in the region, and by increasing the contribution of foreign investment and economic growth, job opportunities will be created and unemployment rates will be reduced on the island of Sumatra.